Connecting Factors for the Application of Community-Based Total Sanitation in the Work Area of the Blang Bintang Health Center, Aceh Besar - Fitri Arsyaf; Sri Aprilia*; Said Usman (Universitas Syiah Kuala, 2023)
Open defecation behavior occurs due to hereditary habits and habits since childhood. At this time, the government launched a program that is to stop open defecation with the Community-Based Total Sanitation Program. This program is an entry point towards total sanitation and is an effort to break the chain of pollution from human excrement to drinking, eating and other standard water. Community-based total sanitation is expected to be able to change people's habitual attitudes in an effort to improve environmental sanitation conditions. This study aims to determine the factors related to the implementation the program in the work area of the Blang Bintang Health Center, Aceh Besar, Aceh Province. This research is descriptive analytic in nature, carried out using a cross-sectional design method with a quantitative approach. The population in this study is the community in the working area of the Blang Bintang Health Center with a population of 1,990 people. The populations of samples were 97 respondents and data analysis used the Chi-Square Test. The results of the study gave respondents the first pillar of good Community-Based Total Sanitation implementation of 63.9%, respondents with less knowledge of 58.8%. In general, respondents with high school education were 69.1%, respondents' behavior towards the program was known 67% to have a positive attitude, 58.8% respondents stated that the role of health workers played a role, 69.1 the role of community leaders was more dominated respondents stated that they lacked participation of 64.9% that respondents had facilities